Non – Formal Education Activities For The Enhancement Of Knowledge And Skills: Investigation Of Non-Explicit Motives For Participation - Koskeris, Andreas; Karalis, Thanassis (European Scientific Journal, ESJ, 2016)
In recent years, more and more adults are seeking for opportunities for additional professional engagement and strengthening their position. Non-formal education offers such a pathway since they are designed to better suit the specific needs of adults. But to make this possible, it is important to direct the relevant scientific research towards analytical investigation of needs and incentives which motivate adults to participate in non-formal education. This investigation is useful to be directed in points beyond the obvious (e.g. acquisition of additional qualifications) to identify particular issues (e.g. need for communication) which should be taken into account for the design of efficient seminars. The purpose of this study was to contribute to the above direction by identifying individual approaches and social needs which affect participation in such actions. By focusing on specific subjects of training, literature study and surveying using questionnaires and focused interviews, it was revealed that apart from the obvious goals of acquiring new knowledge and skills, there are other "internal" needs of adults who urge them to participate in seminars. These have to do mainly with two categories of needs: - The strengthening of self-confidence in relation with continuous developments of our time - The need to improve and strengthen social relations These findings are an important basis for feedback on specific elements that are not often recorded and which should be taken into account during the needs analysis in order to design adult education activities.